Analysis of tourists' risk perceptions in tour destination selection: Bangladesh ecotourism perspective - Rahman, Mohammad Moshiur; Haque, A. K. M. Ahasanul (Editura Universitatii din Oradea, 2024)
Abstract: Ecotourism is the sustainable choice of natural resources with the potential for low-cost funding approaches. As ecologically and socially responsible tourism, it promotes biodiversity while conserving the environment and society. To encourage the development of ecotourism and the advancement of indigenous communities and their resources, it is essential to examine the factors tourists consider when selecting a destination. Therefore, this study explores the critical factors of potential risk in selecting ecotourism destinations in the narrow and specific sphere. As a quantitative study, it used a sample of 377 tourists to investigate the relationship between different constructs. In this regard, SPSS-AMOS was used for data analysis. The findings highlight the importance of factors that influence tourists' decisions, which are greatly affected by risk factors; thus, it is also imperative for the Bangladesh government, policymakers, and tourism management to address this, leading to an upsurge of tourists in ecotourism destinations. These are also crucial for assisting stakeholders in understanding how tourists perceive and guide ecotourism potential and reducing the impact of confrontations.